A Review on Psychotria calceata E.M.A. Petit and its Botanical Characteristics and Traditional Uses - Ngolsou, Francis; Nounaferi, Awa Silué Gnieneferetien; Ouoba, Kampadilemba; Diboue, Patrick Hervé Betote; Nga, Nnanga; Semde, Rasmané (Current Traditional Medicine, 2025)
The genus Psychotria, comprising approximately 1,834 species globally, represents the largest genus within the Rubiaceae family. A substantial number of these species are indigenous to West and Central Africa, notably Cameroon, where comprehensive scientific investigations are, however, notably lacking. Yet, the therapeutic and dietary applications of these species are likely to find a potential justification of their pharmacological attributes, as attested by some studies. It goes without saying that a comprehensive review on the utilization of Psychotria calceata E.M.A. Petit in traditional medicine vis-à-vis its pharmacological properties remains an unexplored territory, and is needed to be investigated. The primary objective of this investigation was to compile data pertaining to the botanical characteristics, phytochemical composition, toxicity and traditional uses of Psychotria calceata. This endeavor aimed to establish a rigorous scientific database and identify areas warranting further research. Relevant information on Psychotria calceata, spanning from 1964 to August 2022, was systematically collected from various scientific databases, encompassing Scopus, Research Gate, SCIENCEDOMAIN, Google Scholar, PubMed, Research4Life (Hinari), Web of Science, ScienceDirect, Current Content Connect, Springer Link, Global Plants, Cochrane Library, and Scirus. Validation of scientific nomenclature was conducted using The World Flora Online. Eight families of secondary metabolites were identified in the aqueous extract of Psychotria calceata leaves. These families included alkaloids, phenolic compounds, flavonoids, tannins, glycosides, coumarins, anthocyanins, and saponins. In addition, in vivo toxicological studies of these same extracts indicated a lethal dose 50 (LD50) of over 5.000 mg/kg body weight, allowing the classification of Psychotria calceata as non-toxic. Histological examination of sections of the main purifying organs, the kidneys, liver, and spleen, corroborated this result, revealing the absence of structural abnormalities within these organs. Psychotria calceata has emerged as a repository of diverse chemical compounds endowed with a range of pharmacological activities. It also holds a prominent position in traditional medicine and dietary practices. However, the nexus between these chemical constituents and the pharmacodynamics of Psychotria calceata remains unestablished due to the paucity of experimental investigations. Consequently, further studies on Psychotria calceata are imperative, with the aspiration of unlocking scientific discoveries and advancing our understanding in this domain.
Keywords: E.M.A